Agglomeration economies in the neighbourhood? Evidence from German cities - Uwe Neumann; Helmut Geißler; Peter Jakubowski (Local Economy, 2013)
In urban renewal policy, it has become a widespread goal to revitalise neighbourhood economies. The rationale for these measures derives, to a great extent, from the concept of regional economic clusters, and, not surprisingly, one of their key objectives is to activate local inter-firm cooperation. This article examines the neighbourhood-related requirements and commitment of small firms. It draws on the results of a case study incorporating five German cities in which the neighbourhood-oriented applicability of economic policy was put to the test. As expected, it is unlikely for most small enterprises in urban renewal areas to engage in inter-firm cooperation focusing on the transfer of highly specialised knowledge. However, many small firms in inner city quarters appreciate neighbourhood characteristics as important location factors, and willingness to support local improvement efforts is relatively high, particularly among firms which operate successfully. The study suggests that there is a case for public policy to encourage small firms to participate in neighbourhood-based initiatives.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; local economic policy; neighbourhood; networks; small firms